If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 23 = 5 Reorder the terms: 23 + -3x = 5 Solving 23 + -3x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -3x = 5 + -23 Combine like terms: 23 + -23 = 0 0 + -3x = 5 + -23 -3x = 5 + -23 Combine like terms: 5 + -23 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| 5p+5(-5-3p)= | | 2x+2x-14=x+9+x+2+x-7 | | 9(4+v)+32v=11v | | 1/4(8x-12)-20 | | 10u+20=170 | | 2.3(x+1.4)=-99.66 | | 3600=(1/x) | | -4-x=8+3x | | 2x+6(3x-6)=64 | | x=1.2/40.8 | | 1/2(2x-2) | | 2x+3(5x+17)=170 | | 1.2=40.8 | | y=(.5x-3)x(.5x-3)x(.5x-3) | | 2x-6=-x+9 | | y=43-3/4 | | x/1.2=40.8 | | -4(5-4y)=9y+50 | | 5x+2(4x+4)=86 | | 3x-4=4x-5 | | x=3/5/1/4 | | 3.81=2x-2.31 | | x=3/5*1/4 | | -2x-3=-3x-3x+1 | | 3/10-1/6= | | 5x+3(x+6)=74 | | 2y^2-4y^3=0 | | .4(a+3)=2 | | -14-3x=16+2x | | 14=3s-4b | | x+5-5=17-5 | | log(6+x)+log(6-x)-logx=2 |